Cloud computing SaaS, PaaS, laaS, virtualization, business models, mobile, security and more - Jamsa, Kris (Jones and Bartlett India Pvt.Ltd, 2013)
This book hands on introduction to cloud technologies which is changing the way businesses and users interact with computers and mobile devices